2007
DOI: 10.1097/01.sla.0000251707.32332.c1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-related Infections in Battlefield Casualties From Iraq

Abstract: Similar to the Vietnam War experience, gram-negative rods, particularly Acinetobacter species, accounted for the majority of wound infections cared for on USNS Comfort during Operation Iraqi Freedom. Multidrug resistance was common, with the exception of the carbapenem class, limiting antibiotic therapy options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
130
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(141 citation statements)
references
References 27 publications
7
130
0
2
Order By: Relevance
“…Reporting findings in line with those of Yun et al [67] and Petersen et al [64], the authors demonstrated that the organism was commonly found in the deployed hospital environment, and particularly in those hospitals dealing with patients who were local nationals. They found that infection with A. baumannii strongly correlated with the number of host nation patients being treated both in the intensive care unit and on the wards.…”
Section: Infection In Conflict Wounded-evidence From Recent Conflictssupporting
confidence: 77%
See 1 more Smart Citation
“…Reporting findings in line with those of Yun et al [67] and Petersen et al [64], the authors demonstrated that the organism was commonly found in the deployed hospital environment, and particularly in those hospitals dealing with patients who were local nationals. They found that infection with A. baumannii strongly correlated with the number of host nation patients being treated both in the intensive care unit and on the wards.…”
Section: Infection In Conflict Wounded-evidence From Recent Conflictssupporting
confidence: 77%
“…In an analysis of 211 battlefield casualties evacuated after forward surgical care in Iraq, Petersen et al [64] detail the microbiology of 53 war wounds, predominantly to the extremities. Eighty-five per cent of overall admissions were Iraqi nationals.…”
Section: Infection In Conflict Wounded-evidence From Recent Conflictsmentioning
confidence: 99%
“…ince the initial widespread use of antibiotics in hospitals during the 1930s and subsequently on multiple battlefields, Gram-negative bacteria resistant to many first-generation cell wall-targeting antibiotics are now the predominant cause of traumatic wound and burn infections (1)(2)(3). Complications encountered during treatment arise in part due to the emergence of multidrug-resistant (MDR) A. baumannii isolates (4-7) whose resistance allows them to disseminate, giving rise to septic shock and disseminated intravascular coagulation (DIC).…”
mentioning
confidence: 99%
“…One of these molecules is the soluble pattern recognition receptor designated pentraxin 3 (PTX3), which recognizes and interacts with a variety of pathogen/damage-associated molecular patterns (PAMP/DAMP) eliciting protection against select pathogens, e.g., Pseudomonas aeruginosa and Aspergillus fumigatus, but not Escherichia coli (2,(19)(20)(21)(22). Additionally, PTX3 has been shown to opsonize pathogens, thus enhancing complement activation and phagocytosis during bacterial and fungal infections, aiding in pathogen clearance through recruitment of C1q and stimulation of the Fc␥ receptor, respectively (16,(18)(19)(20)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Prior to admission, patients followed a complex aeromedical evacuation/hospitalization process as previously described (29,30), except that forward hospitals were in Iraq and Landstuhl, Germany (Landstuhl Regional Medical Center [LRMC]), for this study.…”
mentioning
confidence: 99%